Transformasi Emosi Akademik dan Berpikir Kritis Melalui Augmented Reality dalam Pembelajaran Berbasis Proyek: Sebuah Analisis Rasch Stacking-Racking - Khaerani; Lukman A.R Laliyo; Rustam I Husain (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to evaluate the effectiveness of the Augmented Reality (AR)-integrated Problem-Based Learning (PBL) model on students' academic emotions and critical thinking skills in the topic of Matter and Its Changes. The primary background for this intervention was the low level of student engagement and the difficulty of visualizing abstract science concepts at SMP Negeri 2 Gorontalo. The research employed a quasi-experimental method with a pretest-posttest control group design involving 124 seventh-grade students divided into experimental (n=62) and control (n=62) groups. Data were collected through academic emotion questionnaires (30 Likert-scale items) and two-tier critical thinking tests (16 items), which were then analyzed using the Rasch Model via stacking and racking techniques to ensure data linearity in logit units. The analysis results indicate that integrating AR into PBL significantly increased students' positive academic emotions, with 70.97% of experimental students showing significant improvement, and accelerated critical thinking ability by 1.28 logits compared to 0.44 logits in the control class (Mann-Whitney U, p < 0.001). These findings confirm that AR's immersive visualization functions as cognitive scaffolding that simultaneously strengthens students' affective engagement and analytical thinking, consistent with the Control-Value Theory framework. This study concludes that AR-PBL is an effective intervention for simultaneously transforming affective and cognitive dimensions in junior high school science learning. The findings underscore the importance of integrating immersive technology into the science curriculum to support deeper conceptual understanding of abstract material.